The PENGARUH RASIO SOLVABILITAS, RASIO LIKUIDITAS DAN RASIO PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022-2024: Ekonomi Manajemen Keuangan - Ainia, Risna Nur; Muttafiyah, Siti Rifqiyatul; Wulandari, Ika (Jurnal Istiqro, 2025)
The value of a company is often regarded as a key indicator that influences investors’ decisions in making investments. This study aims to analyze the impact of solvency, liquidity, and profitability on the value of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. The research employs a quantitative approach with an associative method. The sample was taken using a census method, covering all pharmaceutical subsector companies listed on the IDX over the three-year period, resulting in a total of 30 data points. The data used were secondary data obtained from the annual financial statements of the pharmaceutical companies, which were then processed and analyzed using SmartPLS version 4.0. The analysis results indicate that solvency has a positive but not significant effect on the company’s value, whereas liquidity and profitability have a positive and significant effect.